LL-37 boosts immunosuppressive function of placenta-derived mesenchymal stromal cells - Bravo, Martha Oliveira (2016)
Background: Although promising for graft-versus-host disease (GvHD) treatment, MSC therapy still faces important challenges. For instance, increasing MSC migratory capacity as well as potentializing immune response suppression are of interest. For GvHD management, preventing opportunistic infections is also a valuable strategy, since immunocompromised patients are easy targets for infections. LL-37 is a host defense peptide (HDP) that has been deeply investigated due to its immunomodulatory function. In this scenario, the combination of MSC and LL-37 may result in a robust combination to be clinically used. Methods: In the present study, the effects of LL-37 upon the proliferation and migratory capacity of human placenta-derived MSCs (pMSCs) were assessed by MTT and wound scratch assays. The influence of LL-37 over the immunosuppressive function of pMSCs was then investigated using CFSE cell division kit. Flow cytometry and real-time PCR were used to investigate the molecular mechanisms involved in the effects observed. Results: LL-37 had no detrimental effects over MSC proliferation and viability, as assessed by MTT assay. Moreover, the peptide promoted increased migratory behavior of pMSCs and enhanced their immunomodulatory function over activated human PBMCs. Strikingly, our data shows that LL-37 treatment leads to increased TLR3 levels, as shown by flow cytometry, and to an increased expression of factors classically related to immunosuppression, namely IDO, IL-10, TGF-β, IL-6, and IL-1β. Conclusions: Taken together, our observations may serve as groundwork for the development of new therapeutic strategies based on the combined use of LL-37 and MSCs, which may provide patients not only with an enhanced immunosuppression regime, but also with an agent to prevent opportunistic infections.